Cross‐country differences in age trends in alcohol consumption among older adults: a cross‐sectional study of individuals aged 50 years and older in 22 countries. (25th November 2020) - Calvo, Esteban; Allel, Kasim; Staudinger, Ursula M.; Castillo‐Carniglia, Alvaro; Medina, José T.; Keyes, Katherine M.
Abstract: Background and Aims: Age‐related changes in physiological, metabolic and medication profiles make alcohol consumption likely to be more harmful among older than younger adults. This study aimed to estimate cross‐national variation in the quantity and patterns of drinking throughout older age, and to investigate country‐level variables explaining cross‐national variation in consumption for individuals aged 50 years and older. Design: Cross‐sectional observational study using previously harmonized survey data. Setting: Twenty‐two countries surveyed in 2010 or the closest available year. Participants: A total of 106 180 adults aged 50 years and over. Measurements: Cross‐national variation in age trends were estimated for two outcomes: weekly number of standard drink units (SDUs) and patterns of alcohol consumption (never, ever, occasional, moderate and heavy drinking). Human Development Index and average prices of vodka were used as country‐level variables moderating age‐related declines in drinking. Findings: Alcohol consumption was negatively associated with age (risk ratio = 0.98; 95% confidence interval = 0.97, 0.99; P ‐value < 0.001), but there was substantial cross‐country variation in the age‐related differences in alcohol consumption [likelihood ratio (LR) test P ‐value < 0.001], even after adjusting for the composition of populations. Countries' development level and alcohol prices explained 31% of cross‐country variability in SDUs (LR test P ‐value < 0.001) but did not explain cross‐country variability in the prevalence of heavy drinkers. Conclusions: Use and harmful use of alcohol among older adults appears to vary widely across age and countries. This variation can be partly explained both by the country‐specific composition of populations and country‐level contextual factors such as development level and alcohol prices.